FUNGSI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU - A. Dedi Nopembri (Manajer Pendididikan, 2015)
This study is aimed to describe the function of head master in increasing teacher’s performance at Junior High School 2 Lubuklinggau. The method of study used was descriptivequalitative. The subjects of the research were a principal and teachers. The technique of data collecting used is interview, observation and documentation. It can be, concluded that: (1) as a leader, principal has been effectively applied to motivate, influence, and direct teacher’s activities at school, (2) as a motivator, the principal was able to urge teachers increasing their performance, (3) as a supervisor, he had guided teachers effectively, (4) as a manager, the principal work together with teachers, and urging their involvement all teachers in school program, (5) his function, as an administrator had gone well.Keywords: principal, function, teachers, performance